Conditionals and inferential connections: toward a new semantics. (2nd July 2020) - Douven, Igor; Elqayam, Shira; Singmann, Henrik; Wijnbergen-Huitink, Janneke van
Abstract: In previous published research ("Conditionals and Inferential Connections: A Hypothetical Inferential Theory, " Cognitive Psychology, 2018), we investigated experimentally what role the presence and strength of an inferential connection between a conditional's antecedent and consequent plays in how people process that conditional. Our analysis showed the strength of that connection to be strongly predictive of whether participants evaluated the conditional as true, false, or neither true nor false. In this article, we re-analyse the data from our previous research, now focussing on the semantics of conditionals rather than on how they are processed. Specifically, we use those data to compare the main extant semantics with each other and with inferentialism, a semantics according to which the truth of a conditional requires the presence of an inferential connection between the conditional's component parts.